Musical Exphrasis in Ukrainian Organ Music (on the Example of “Sound of the Pinzel” by Bohdana Frolyak) - Kupina, Daryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the study is explained by the need to expand the understanding of the process of transmedial communication (and ekphrasis in particular), throw the prism of Ukrainian organ music. In this context, the problem of musical ekphrasis is considered on the example of the piece for organ and strings of the Ukrainian composer Bohdan Frolyak “Sound of Pinzel”. Main objective of the study is to identify ways to recode visual material into music in the piece “Sound of Pinzel” by Bohdana Frolyak. The theoretical basis of the article has certain researching sources by S. Bruhn and T. Tsaregradskaya, which explore the concept of musical ekphrasis, methods and principles of re-coding artistic information. The research methodology is based on a combination of the method of intermediate, holistic and contextual types of analysis, which allow through the analysis of visual material to approach the understanding of a musical work. Results / findings and conclusions. Musical ekphrasis means the translation of a work of visual art to the symbolic plane of music while preserving the compositional and / or syntactic qualities of the original source. Types of intersemiotic transmedialization are interpretation, recontextualization, game setting, association, and so on. It is noted that in the Ukrainian organ music the tendency of transmedial search is realized first of all through the appeal to ekphrasis. This thesis is confirmed by the analysis of the work of B. Frolyak, which was prompted by the sculptures of the Ukrainian baroque master Pinzel. It turns out that in addition to the «spiritual programmaticity» embedded in the plots of the sculptures, as part of the church ensemble, in the musical opus becomes obvious transmedial aspect, which acquires the features of musical ekphrasis. The piece “Sound of Pinzel” is based on the principle of spiritual association and the embodiment of structural and semantic parallels. It is pointed out that the sharp lines of the master's sculptures are conveyed in the music and the inner impulse and expression of movement is felt as a characteristic feature of the late Baroque style. Other features of ekphrasis are images in the outlines of themes (chapter II) of the sculptural plot or the use of allusion to the chorale (chapter VI) as a prayer symbol and so on. The conclusions emphasize the need to expand and detail the transmedia study of musical works, including the features of musical ekphrasis.